Estudo comparativo de ensaios bacteriológicos para confirmação da presença de Mycobacterium bovis em amostras teciduais de bovino com lesões compatíveis com tuberculose - Marina de Azevedo Issa (2015)
The definitive diagnosis of animal tuberculosis demands the isolation of its etiological agent. However, there is no consensus on the best methodology for isolation of Mycobacterium bovis in Brazil. This study evaluated the most used decontaminants and culture media in the country, in order to identify the best combination for the Brazilian samples. Three decontaminants - 2% sodium hydroxide (NaOH) (w/v), 0.75% hexadecilpiridinium chloride (HPC) (w/v) and 5% sulphuric acid (H2SO4) (v/v) and four culture media - 7H11 Middlebrook with additives and OADC supplement A (7H11 A), the same medium with another supplement trademark (7H11 B), tuberculosis blood agar (B83) and Stonebrinks medium (SB) were compared. Regarding the isolation success, there were no significant differences between the decontaminants-media combinations, except 7H11A combined to any decontaminant. However, the mean colonies score was significantly greater when the samples were decontaminated with the acid and inoculated in 7H11 B or SB, without significant difference between them, although colonies appeared earlier on 7H11B. The trademark of OADC supplement influenced the isolation rate and the number of isolated colonies in Middlebrook 7H11. An incubation time of four weeks was required to detect all positive samples in 7H11 B after decontamination with 5% H2SO4 but there was an increase in the number of colonies until the sixth week of incubation. Overall, the best strategy for the primary isolation of M. bovis from Brazilian samples was the decontamination with 5% H2SO4 (final concentration) and inoculation in Middlebrook 7H11 medium formulated with OADC supplement B.